PENGGUNAAN MEDIA FOTO PERINGATAN HUTKE 64 PROKLAMASI KEMERDEKAAN RI UNTUK MENINGKATKAN PEMAHAMAN MAKNA PROKLAMASI - Maryanto Maryanto (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2010)
Understanding the independence proclamation is an abstract thing which most SMP Negeri 2 Polosari student find it difficult to discern. That was the reason behind this classroom action research. The aim was to improve the student understanding of the meaning of independence proclamation for them and to motivate learning. This was done to class VII B, with 34 students. Consisted of four stages (planning, action, observation, and reflection). In the action stage students had to discuss a topic in which photographs of the 64th independence celebration in pemalang was the focus. Data was taken through observation, questionaire and test. The result was that the use of photographs improved students understanding on the meaning of independence proclamation. This was based on the fact that students participation increased from 71,42% in cycle I to 90,47% in cycle II. The result of the questionaire and the observation showed increase in student motivation from 70,35% in cycle I and 79,85% in cycle II. Similiar tendency was also shown the average result of the test which was 66,62 in cycle I and 75,44 in cycle II. This also hapenned to the mastery level which showed increase from 50% in cycle I and 91,18% in cycle II. Key Words: photo’s medium, meaning of the independence proclamation